PELATIHAN PENCEGAHAN DAN MENEKAN PLAGIARISM PENULISAN ILMIAH - Idel Waldelmi; Afvan Aquino; Wita Dwika Listihana (Jurnal Abdimas Bina Bangsa, 2023)
The implementation of the service carried out online / plagiarism seminar, the results obtained state that the PKM Training on Prevention and Suppression of Plagiarism in Scientific Writing that has been carried out, can be concluded, that in an effort to prevent and suppress plagiarism this can be done by providing training, education, intervention, sanctions, and mutual awareness both individually and in groups. This can be done by increasing knowledge, understanding and belief in the impact of plagiarism in scientific writing. The participants reached 163 participants from various campus backgrounds, both local and national